Attitudes of pregnant women and healthcare professionals towards clinical trials and routine implementation of antenatal vaccination against respiratory syncytial virus: a multi-centre questionnaire study - Wilcox, CR; Calvert, A; Metz, J; Beadon, K; Snape, MD (Lippincott, Williams and Wilkins, 2019)
Introduction: Respiratory syncytial virus (RSV) is a common cause of infant hospitalization and mortality. With multiple vaccines in development, we aimed to determine: (1) the awareness of RSV among pregnant women and healthcare professionals (HCPs), and (2) attitudes toward clinical trials and routine implementation of antenatal RSV vaccination.